Gender and generation in the world's labor force : module one: international and national trends (USAID WashingtonUS, 1994)
Analyzes differences in the changing labour force in world regions and selected countries. Provides an account of the current size and age/sex composition of the world's labour force, by region, and its projected growth to the year 2010. Dicusses the changes in occupational distributions and female employment in particular sectors and concludes with a brief analysis of gender differences in hours of work.
DC